TEXT PICTURE TRANSLATION INTO SPEECH IN DESIRED LANGUAGE - akkala, Anugna; S. , Prem kumar (International Journal of Psychosocial Rehabilitation, 2020)
Text-to-speech is a technology through which computers are made to speak. If a study is performed like listening or reading, and which is more effective, the definitely answer is listening, because people will understand more by listening than reading. In much research, it is proved that listening improves imagination power. The main aim is to provide speech output in real time for blind people when they give printed text as input. This text-to-speech requires two technologies: optical character recognition (OCR) and text-to-speech conversion. The former technique is used for extracting text from images. The later technology converts the extracted text into speech. In any reading assistant system, the first and most important function is text information extraction, and this is the integral part of OCR. To recognize words, OCR is used.